A framework for sustainable port planning in inland ports: a multistakeholder approach - Michael Dooms; Cathy Macharis (European Regional Science Association (ERSA), 2003)
In the European Union, all levels of government are convinced that an accelerated development of a modal shift towards inland navigation is one of the key requirements for reducing congestion and environmental externalities. This is becoming increasingly important, given the fast growing (road) transport needs at the macro-economic level. It is expected that inland ports can play a crucial role in achieving such a modal shift. However, many inland ports are confronted with important spatial, socio-economic and regulatory constraints as, historically, they have been located in the centre of large (capital) cities and other high density urban regions. As a result, they face constant pressure from a variety of stakeholders (urban residents, leisure industry, ecological movement, ?) and they must continuously defend their right of existence. The aim of this paper is to present a conceptual framework for inland port planning that builds upon a multistakeholder - multicriteria approach, which takes into account all the short-term and long-term stakeholder preferences and objectives, in order to realize sustainable port development. This framework will also deal with the complexity of the port function in urban regions, as these ports/activities are in most cases dispersed over the urban region, whereby each port ?zone? has its own specific spatial, socio-economic, and regulatory characteristics. The combination of existing literature in the fields of (urban) port development and multicriteria analysis, and empirical evidence, gathered during the development of a strategic masterplan for the inland Port of Brussels, will permit the formulation of a new approach to inland port development.
Keywords: 330